Influence of Metoprolol Treatment on Sympatho-Adrenal Activation of Fibrinolysis - Larsson, P T; Wiman, B; Olsson, G; Angelin, B; Hjemdahl, P (Thrombosis and Haemostasis, 1990)
The effects of mental stress (a colour word conflict test, CWT) and adrenaline infusions (0.1 and 0.4 nmol kg−1 min−1) on t-PA activity, t-PA antigen, PAI-1 activity and PAI-1 antigen were studied in 18 healthy male volunteers. Furthermore, the effects of metoprolol (200 mg/day during 1 week) or placebo (double-blind cross-over study) on fibrinolytic responses to sympatho-adrenal activation, and relationships between fibrinolysis and blood lipids were investigated.Low and high dose adrenaline infusions yielding plasma adrenaline levels of 0.9 ± 0.1 and 3.4 ± 0.4 nmol/1, respectively, dose-dependently increased t-PA levels with a concomitant decrease in PAI-1 levels. A similar, but weaker, fibrinolytic response seemed to occur during CWT when plasma adrenaline levels were only moderately increased (to 0.4 ± 0.1 nmol/1). Metoprolol treatment did not influence the resting levels of the fibrinolytic variables studied, but tended to enhance the t-PA response to CWT and further reduce PAI-1 during adrenaline infusion. Metoprolol treatment was not accompanied by any rise in PAI-1 levels despite drug induced elevations of triglyceride levels. Thus, the present study shows that sympatho-adrenal activation increases fibrinolytic activity in vivo and that meto prolol treatment may have a favourable influence on this activity.